1996
DOI: 10.1111/j.1651-2227.1996.tb14258.x
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility, obstetric and gynaecological history in coeliac disease: a case control study

Abstract: Objectives: The purpose of this study was to investigate the incidence of infertility, abortions and perinatal mortality, age at menarche and menopause in coeliac disease. Method: This was a case control study in which patients and controls, matched for age and sex, were sent questionnaires about their fertility profile and other obstetric and gynaecological problems. All 80 patients and 70 controls replied, but only 68 pairs could be matched for this study. Results: The mean age of menarche in patients was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
1
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 4 publications
0
76
1
14
Order By: Relevance
“…47 Moreover, there is also a greater frequency of recurrent miscarriages (mainly in the first 3 months of pregnancy), stillbirth and neonatal death. 48 In males, impotence, decreased sexual activity, infertility, abnormalities of sperm morphology and motility may be expressions of CD. 49,50 Another presentation of atypical CD is so-called celiac hepatitis, characterized by a gluten-dependent increase in serum transaminases without abnormality of any other liver functions.…”
Section: Introductionmentioning
confidence: 99%
“…47 Moreover, there is also a greater frequency of recurrent miscarriages (mainly in the first 3 months of pregnancy), stillbirth and neonatal death. 48 In males, impotence, decreased sexual activity, infertility, abnormalities of sperm morphology and motility may be expressions of CD. 49,50 Another presentation of atypical CD is so-called celiac hepatitis, characterized by a gluten-dependent increase in serum transaminases without abnormality of any other liver functions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adverse effects on the mother may also occur, as indicated by a recent German study which demonstrated that the rate of cesarean delivery is increased if the parents have CD [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are many problems seen in CD that may affect a woman's ability to achieve a pregnancy like delay of menarche and menstrual disorders (ovulation problems), putting in mind sub fertility may be immune mediated, it is near to some studies, conducted in Europe and Mid east, it emphasized, CD has been associated with sub fertility, as well as it is consistent with Canadian study in 2008, revealed that, CD may be a significant contributor to fertility problems in women, as well as studies that carried out by Sher et al ,. Collin and colleagues and Certain study that was performed in Sardinia by Meloni et al, Swedish study concluded that women with CD overall had normal fertility and this explained by the modality of life of Swedish women [19][20][21].…”
Section: Citation: Hassan Sm Yassin K Zakaria Na (2017) Reproductivmentioning
confidence: 99%
See 1 more Smart Citation
“…En la mujer, la enfermedad celiaca ha sido asociada a alteraciones obstétri-cas y ginecológicas, como infertilidad, abortos de repetición, bajo peso al nacimiento, menor duración de la lactancia materna, entre otros. Sin embargo, los datos de las series publicadas no siempre coinciden en estas apreciaciones (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
unclassified